Responsibility for campaign grant funds in the 2024 presidential election: Hifdzul Mal's perspective - Manik, Indra Prawira; Zulham, Zulham (The International Journal of Politics and Sociology Research, 2024)
President Joko Widodo has made a decision regarding the voting day for the General Election of 2024. The substantial campaign fund required for the presidential election necessitates donors for campaign financing. However, issues arise in the implementation concerning the unclear origin of campaign grant funds. "Hifdzul mal" or protection is one of the concepts derived from Sharia maqasid, obligating the proper preservation and protection of property as a means of worshiping Allah. In Islam, the safeguarding of wealth prohibits theft, deception, hoarding, and engaging in activities related to usury. The acquisition of wealth must adhere to Sharia-compliant efforts.This research utilizes a normative legal research method with a statutory approach and a conceptual approach. The data collection employs library research instruments, and qualitative methods are used to gain an understanding of the researched issues. The findings reveal that, in the compilation of laws within the Election Supervisory Agency (BAWASLU) and the General Election Supervisory Board (PKPU) Acts regarding the supervision of campaign funds for general elections, several provisions align with the concept of "Hifdzul Mal" (wealth protection). It is emphasized that the management of campaign funds is highly relevant to the concept of value in Hifdzul Mal. Individuals or groups involved in fraud related to campaign funds face legal consequences based on the principles of Hifdzul Mal and the Election Supervisory Agency (BAWASLU) and General Election Supervisory Board (PKPU) Acts. This legal foundation underscores the importance of safeguarding wealth and the severity of the sins committed by violators